Rome, global dreams and the international origins of an empire - Davies, Sarah H. (Impact of Empire;, 2019)
In Rome, Global Dreams, and the International Origins of an Empire, Sarah Davies explores how the Roman Republic evolved, in ideological terms, into an "Empire without end." This work stands out within Roman imperialism studies by placing a distinct emphasis on the role of international-level norms and concepts in shaping Roman imperium. Using a combination of literary, epigraphic, and numismatic evidence, Davies highlights three major factors in this process. First is the development, in the third and second centuries BCE, of a self-aware international community with a cosmopolitan vision of a single, universalizing world-system. Second is the misalignment of Rome's polity and concomitant diplomatic practices with those of its Hellenistic contemporaries. And third is contemporary historiography, which inserted Rome into a cyclical (and cosmic) rise-and-fall of great power.